Comparative Analysis of the Speed of the Sorting Method on Google Translate Indonesian-English Using Binary Search - Ekowati, Maria Atik Sunarti; Nindyatama, Zefanya Permata; Widianto, Widianto; Dananti, Kristyanan (International Journal of Global Operations Research, 2022)
In Indonesia, English is a compulsory subject for students. This course is an uninteresting subject and tends to be difficult for students to understand. Meanwhile, on the other hand, international issues are often discussed, namely English which is Students must know and be fluent in reading, writing and communication. The basic idea of research objectives, comparing the sorting process using two different algorithms, namely bubble sort and Merge Sort. The basic model of the research method Comparative Analysis of the Speed of the Shorting Method on Google Translate Indonesian-English Using Binary Search. Sorting, Sorted (ordered according to certain rules/rules), and the data is presented in sorted form, as said in dictionaries, and files in a directory. The algorithm used for sorting is bubble sort, which is an element comparison operation that is exchanged for other elements until the end of the data series is reached, until no more elements are swapped. Results for find out how well the performance speed of the bubble sort algorithm is in sorting data.